313 Understanding home injuries: Results from a Ugandan household survey and risk assessment. (20th November 2022) - Puvanachandra, Prasanthi; Ssemugabo, Charles; Bachani, Abdul; Kobusingye, Olive; Peden, Margaret
Abstract : Background: Globally, thousands of children lose their lives to unintentional injuries every year. Injuries occurring at home to under 5s can be prevented through providing safety equipment but these need to be context-specific. Methods: As part of the quantitative component of a larger mixed-methods study, we carried out a survey of households with children under 5 years coupled with a home risk assessment to describe the incidence of childhood household injuries and prevalence of modifiable household risk factors in Jinja. Results: The survey of 615 households indicated that there had been 879 injury events amongst under 5s in the preceding 12 months. The majority occurred within the compound of the home with 57% fall-related and 23% burn injuries being reported. 87% of households had a stove within reach of the child and 37% had an accessible open fireplace. 71% of the households had no anti-slip mats on the floor and among the houses that had stairs only 16% were blocked by a gate or barrier. There was a significant association between the decreased risk of injury and the presence of a separate kitchen and when matches or an open fire were not within reach of a child. Conclusion: Unintentional injuries among under 5s are a significant public health issue in Jinja, Uganda. Our study showed that modifiable risk factors were associated with an increase in injuries. These findings will inform the development of a culturally appropriate set of interventions and provide accurate incidence rates for a future intervention trial.